2-Phenylbenzofuran derivatives alleviate mitochondrial damage via the inhibition of beta-amyloid aggregation - Lee, Yun Suk; Kim, Hye Yun; Youn, Hea Mee; Seo, Jae Hong; Kim, YoungSoo; Shin, Kye Jung (Pergamon Press Ltd., 2013)
To obtain modulators for reducing mitochondrial damage by the inhibition of A beta oligomer formation, 2-phenylbenzofuran derivatives were designed and prepared. Their inhibitory activity against A beta fibril formation was screened using ThT fluorescence assay, and the effect of derivatives on mitochondrial function was evaluated using JC-1 and MTT assay. 2-Phenylbenzofuran derivatives with dimethylamino group at p-position had an excellent inhibitory activity against A beta fibril formation. Particularly, compound 19m alleviated mitochondrial damage remarkably and possessed protective effects against A beta-induced cytotoxicity. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: LONG-TERM POTENTIATION; FERULIC ACID; A-BETA; ALZHEIMERS-DISEASE; OXIDATIVE STRESS; FIBRIL FORMATION; IN-VIVO; PEPTIDE; DYSFUNCTION; NEURONS